Between righteous legacy and Pyrrhic victory – an administrator's dilemma. Issue 2 (5th May 2016) - Hudson, Monika; Hunter, Keith O.
Abstract : Synopsis: When do you throw it all away? The first senior female in a male-dominated business school decides it all comes down to a question of principle – and maybe a few others. What is the best balance between her responsibilities to students, family, and the next generation of female leaders? Can she both be true to herself and compromise? What factors should influence this decision? This case brings together questions about power and influence, rational decision-making, leadership, and the intra and inter-personal responsibilities of organizational "firsts." Further, issues related to a university's effort to better compete within the global higher education marketplace, provide a valuable opportunity to explore institutional approaches to promoting diversity, inclusion, and cultural competency. Research methodology: This case, which was developed from primary sources, highlights the array of competing objectives and personal and political tensions involved in university administration. Relevant courses and levels: This case was designed for graduate students in Masters of Public Administration, Masters of Business Administration, Masters of Education in Organizational Leadership, or similar graduate degrees that include significant management and leadership content. Students working with this case should have already completed foundational courses in topics such as organizational management, public policy, leadership, strategic human resources management, or their equivalents within their respective programs of study. Virtually all of the issues raised by this case address core themes, concepts, theses, and theories associated with an accredited graduate program in educational management, business or public administration.